2018
DOI: 10.1208/s12249-018-1139-4
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induction and Antimigratory Activity of Andrographolide Analog (3A.1)-Incorporated Self-Assembled Nanoparticles in Cancer Cells

Abstract: Andrographolide analog, namely 19-tert-butyldiphenylsilyl-8,17-epoxy andrographolide (or 3A.1) has been reported to be a potential anticancer agent for several types of cancer. Due to its poor aqueous solubility, 3A.1 was incorporated within self-assembly polymeric nanoparticles made of naphthyl-grafted succinyl chitosan (NSC), octyl-grafted succinyl chitosan (OSC), and benzyl-grafted succinyl chitosan (BSC). These 3A.1-loaded nanoparticles were nanosized (< 200 nm) and spherical in shape with a negative surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…MET-PLGA-PEG NPs also induced nuclei fragmentation and apoptosis in the treated cancer cells [122]. Other NPs which were reported to induce apoptosis in cancer cells are Nos-mPEG-PLGA NPs [117], NVA polymeric NPs [136], ANZ-PLNP NPs [118], 3A.1-loaded pH-sensitive NPs [132], CS-CPT-NPs [133], 5FU-Chrysin-PLGA-PEG-PLGA NPs [120], and Gemcitabine-loaded NPs conjugated with linoleic acid [143]. Nos-mPEG-PLGA NPs [117] has antiangiogenic properties while NVA polymeric NPs [136] inhibited cellular proliferation.…”
Section: Polymeric Nanomaterials Targeting Various Cancersmentioning
confidence: 96%
See 1 more Smart Citation
“…MET-PLGA-PEG NPs also induced nuclei fragmentation and apoptosis in the treated cancer cells [122]. Other NPs which were reported to induce apoptosis in cancer cells are Nos-mPEG-PLGA NPs [117], NVA polymeric NPs [136], ANZ-PLNP NPs [118], 3A.1-loaded pH-sensitive NPs [132], CS-CPT-NPs [133], 5FU-Chrysin-PLGA-PEG-PLGA NPs [120], and Gemcitabine-loaded NPs conjugated with linoleic acid [143]. Nos-mPEG-PLGA NPs [117] has antiangiogenic properties while NVA polymeric NPs [136] inhibited cellular proliferation.…”
Section: Polymeric Nanomaterials Targeting Various Cancersmentioning
confidence: 96%
“…The enhanced drug delivery of quercetin to the target site was attributed to the improved encapsulation and the sustained release of the drug [131]. Similarly, 3A.1-loaded pH-sensitive chitosan NPs [132] and Cs-CPT NPs [133] specifically targeted and delivered the drugs to colon cancer cells. SVCSNPs was shown to exhibit controlled release of SV, hence increasing the accumulation of drug in intracellular compartments of hepatic cancer cells [134].…”
Section: Polymeric Nanomaterials Targeting Various Cancersmentioning
confidence: 99%
“…56 An andrographolide derivative, 19-tertbutyldiphenylsilyl-8, loaded by nanoparticles-17-epoxyandrographolide (3A.1), had a remarkably lower IC 50 than 3A.1 in HT 29 cells. 60 Liposomal andrographolide dry powder inhalers exhibited stronger activity against Staphylococcus aureus pneumonia than mere andrographolide in rats. 19 Similarly, the antipneumonic activity of andrographolide-βcyclodextrin inclusion complex (AG-β-CD) was better than andrographolide in a pneumonic rat model.…”
Section: New Delivery Systems For Andrographolidementioning
confidence: 97%
“…Encapsulated andrographolide in nanoparticle form was better at treating OVA‐induced asthmatic mice than its no dosage form 56 . An andrographolide derivative, 19‐tert‐butyldiphenylsilyl‐8, loaded by nanoparticles‐17‐epoxyandrographolide (3A.1), had a remarkably lower IC 50 than 3A.1 in HT 29 cells 60 . Liposomal andrographolide dry powder inhalers exhibited stronger activity against Staphylococcus aureus pneumonia than mere andrographolide in rats 19 .…”
Section: Introductionmentioning
confidence: 99%
“…15 The Anticancer activity of AGL was observed by the induction of apoptosis. 16 Chao et al reported that down-regulation of cell growth, apoptosis, anti-angiogenesis, and anti-transformation is the major pathway of AGL to inhibit cancer cell growth. 17 Lim et al exhibited that down-regulation of tyrosine kinase, cyclin kinase, and growth factor and up-regulation of Apoptotic protein is the potential mechanism of AGL against cancerous cells.…”
Section: Anticancer Activitymentioning
confidence: 99%